Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 8.(-5).(-4).2 = 8.20.2 = 8.40 = 320
b) \(1\frac{3}{7}+\left(-\frac{1}{3}+2\frac{4}{7}\right)\)
\(=1\frac{3}{7}-\frac{1}{3}+2\frac{4}{7}\)
\(=\left(1\frac{3}{7}+2\frac{4}{7}\right)-\frac{1}{3}=\left(1+2\right)+\left(\frac{3}{7}+\frac{4}{7}\right)-\frac{1}{3}=4-\frac{1}{3}=\frac{11}{3}\)
c) \(\frac{8}{5}\cdot\frac{-2}{3}+\frac{-5\cdot5}{3\cdot5}\)
\(=\frac{8}{5}\cdot\frac{-2}{3}+\frac{-25}{15}=\frac{-16}{15}+\frac{-25}{15}=\frac{-41}{15}\)
d) \(\frac{6}{7}+\frac{5}{8}:5-\frac{3}{16}\left(-2\right)^2=\frac{6}{7}+\frac{5}{8}\cdot\frac{1}{5}-\frac{3}{16}\cdot4\)
\(=\frac{6}{7}+\frac{1}{8}-\frac{3}{4}=\frac{13}{56}\)
a: \(2^7+\left(x-3^7\right)=5^7-4^7\)
=>\(128+x-2187=78125-16384\)
=>\(x-2059=61741\)
=>\(x=61741+2059=63800\)
c: \(7^2-\left(x+15\right)=5\cdot2^2\)
=>49-(x+15)=5*4=20
=>x+15=29
=>x=14
d: 7^3-7(13-x)=14
=>343-7(13-x)=14
=>7(13-x)=343-14=329
=>13-x=47
=>x=13-47=-34
\(=\frac{5.2^{30}.3^{18}-2^2.3^{20}.2^{27}}{5.2^9.2^{19}.3^{19}+7.2^{29}.3^{18}}\)
\(=\frac{5.2^{30}.3^{18}-2^{29}.3^{20}}{5.2^{28}.3^{19}+7.2^{29}.3^{18}}\)
\(=\frac{2^{29}.3^{18}\left(5.2-3^2\right)}{2^{28}.3^{18}\left(5.3+7.2\right)}\)
\(=\frac{2}{29}\)
\(B=\frac{\left(\frac{1}{5}-\frac{2}{7}\right).\frac{3}{4}-\frac{3}{4}.\left(\frac{1}{3}-\frac{2}{7}\right)}{\frac{1}{5}.\frac{2}{7}-\frac{1}{3}.\left(\frac{2}{7}+\frac{3}{9}\right)+\frac{3}{9}.\frac{1}{5}}\)
\(B=\frac{\frac{3}{4}.\left(\frac{1}{5}-\frac{2}{7}-\frac{1}{3}+\frac{2}{7}\right)}{\frac{1}{5}.\frac{2}{7}-\frac{1}{3}.\frac{2}{7}-\frac{1}{3}.\frac{1}{3}+\frac{1}{3}.\frac{1}{5}}\)
\(B=\frac{\frac{3}{4}.\left(\frac{1}{5}-\frac{1}{3}\right)}{\frac{2}{7}.\left(\frac{1}{5}-\frac{1}{3}\right)-\frac{1}{3}.\left(\frac{1}{3}-\frac{1}{5}\right)}\)
\(B=\frac{\frac{3}{4}.\left(\frac{1}{5}-\frac{1}{3}\right)}{\frac{2}{7}.\left(\frac{1}{5}-\frac{1}{3}\right)+\frac{1}{3}.\left(\frac{1}{5}-\frac{1}{3}\right)}\)
\(B=\frac{\frac{3}{4}.\left(\frac{1}{5}-\frac{1}{3}\right)}{\left(\frac{2}{7}+\frac{1}{3}\right).\left(\frac{1}{5}-\frac{1}{3}\right)}\)
\(B=\frac{\frac{3}{4}.\left(\frac{1}{5}-\frac{1}{3}\right)}{\frac{13}{21}.\left(\frac{1}{5}-\frac{1}{3}\right)}=\frac{\frac{3}{4}}{\frac{13}{21}}=\frac{3}{4}:\frac{13}{21}=\frac{63}{52}\)
b)\(2^{x-1}+5\cdot2^{x-2}=\frac{7}{32}\)
\(2^x:2+5\cdot2^x:2^2=\frac{7}{32}\)
\(2^x:2+2^x:\frac{4}{5}=\frac{7}{32}\)
\(2^x\cdot\left(\frac{1}{2}+\frac{5}{4}\right)=\frac{7}{32}\)
\(2^x\cdot\frac{7}{4}=\frac{7}{32}\)
\(2^x=\frac{7}{32}:\frac{7}{4}=\frac{1}{8}\)
\(2^x=\frac{2^0}{2^3}=2^{-3}\)
\(\Rightarrow x=-3\)
a) \(4^x+4^{x+3}=4160\)
\(\Rightarrow4^x+4^x.4^3=4160\)
\(\Rightarrow4^x.\left(1+4^3\right)=4160\)
\(\Rightarrow4^x.65=4160\)
\(\Rightarrow4^x=64\)
\(\Rightarrow4^x=4^4\)
\(\Rightarrow x=4\)
Vậy \(x=4\)
b) \(2^{x-1}+5.2^{x-2}=\frac{7}{32}\)
\(\Rightarrow2^x.\frac{1}{2}+5.2^x.\frac{1}{4}=\frac{7}{32}\)
\(\Rightarrow2^x.\left(\frac{1}{2}+5.\frac{1}{4}\right)=\frac{7}{32}\)
\(\Rightarrow2^x.\frac{7}{4}=\frac{7}{32}\)
\(\Rightarrow2^x=\frac{7}{32}:\frac{7}{4}\)
\(\Rightarrow2^x=\frac{1}{8}\)
\(\Rightarrow2^x=2^{-3}\)
\(\Rightarrow x=-3\)
Vậy \(x=-3\)
\(2^{\left(x-1\right)}+5.2^{\left(x-2\right)}=\frac{7}{32}\)
\(\Leftrightarrow2.2^{x-2}+5.2^{x-2}=\frac{7}{32}\)
\(\Leftrightarrow\left(2+5\right).2^{x-2}=\frac{7}{32}\)
\(\Leftrightarrow7.2^{x-2}=\frac{7}{32}\)
\(\Leftrightarrow2^{x-2}=\frac{7}{32}:7\)
\(\Leftrightarrow2^{x-2}=\frac{1}{32}=2^{-5}\)
\(\Leftrightarrow x-2=-5\)
\(\Leftrightarrow x=\left(-5\right)+2\)
\(\Leftrightarrow x=-3\)
Vậy \(x=-3\).
Chúc bạn học tốt!
\(x:\left[\frac{8}{5}.\left(\frac{2}{3}\right)^2-\frac{2}{5}\right]=\frac{15}{7}+\frac{6}{5}.\left[\left(\frac{15}{7}\right)^2-\frac{50}{49}\right]\)
\(\Rightarrow x:\frac{14}{45}=\frac{15}{7}+\frac{6}{5}.\frac{25}{7}\)
\(\Rightarrow x:\frac{14}{45}=\frac{15}{7}+\frac{30}{7}\)
\(\Rightarrow x:\frac{14}{45}=\frac{45}{7}\)
\(\Rightarrow x=\frac{45}{7}.\frac{14}{45}\)
\(\Rightarrow x=2\)
Vậy \(x=2.\)
Chúc bạn học tốt!
4:5.2 = x. \(\dfrac{2}{7}\)
=> x. \(\dfrac{2}{7}\) = 4:5.2
x. \(\dfrac{2}{7}\) = \(\dfrac{8}{5}\)
x = \(\dfrac{8}{5}.\dfrac{7}{2}\)
x = \(\dfrac{28}{5}\)
Vậy x = \(\dfrac{28}{5}\)